NSAIDs: General Characteristics, Classification, Pharmacokinetics/ Pharmacodynamics, Clinical Uses and Adverse Effects - Aksoy, A.; Das, Y.K. (Nova Science Publishers, Inc., 2021)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are mainly used as analgesics for slight to moderate pain. NSAIDs are prescribed for the alleviation of pain in patients with infections. They are also used for anti-inflammatory, anti-pyretic, anti-rheumatic, anti-thrombotic and spasmolytic purposes. Their mode of action is based on the inhibition of the cyclooxygenase (COX) enzymes. There are two main COX enzyme types, namely the physiological and inducible types, COX-1 and COX-2, respectively. The effects of NSAIDs vary depending on whether they selectively inhibit the activity of COX-1 or COX-2. NSAIDs that are selective for the COX-2 enzyme generally achieve their therapeutic effects with a lower level of adverse effects. However, non-selective NSAIDs have undesirable effects that include digestive system disorders, decreased renal perfusion and increased tendency to bleed. In this chapter, the general characteristics, classification, clinical uses and adverse effects of NSAIDs are summarized. © 2021 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Adverse Effects; Characteristics; Classification; NSAIDs; Uses